ANALYSIS OF CAPITAL INTENSITY, SALES GROWTH, AND AUDIT COMMITTEE ON TAX AGGRESSIVENESS - Michaela Janice Ved; Julianti Sjarief (SIMAK, 2022)
This study aims to analyze capital intensity, sales growth, and the audit committee on tax aggressiveness. In this study, the population used are companies from the mining sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample selection in this study used purposive sampling method with the number of sample 130 from 36 companies/ The data analysis method used was descriptive statistics and multiple linear regression analysis using SPSS version 26. The results of this study indicate that capital intensity has a positive effect on tax aggressiveness, sales growth has a positive effect on tax aggressiveness, and the audit committee has no effect on tax aggressiveness.